Rasionalitas Penggunaan Tablet Tambah Darah pada Remaja untuk Pencegahan Stunting di Wilayah Kerja Puskesmas Kadatua Timur - Hamzah, Hasty; Rusli, Fitriani; Rurwanti, Ratih; Ilham, Sitti Alfyanita (Universitas Hang Tuah Pekanbaru, 2025)
Efforts have been made by the Kadatua Timur Health Center to implement stunting prevention by providing iron tablets to young girls in 5 villages within the local health center's working area. A study was conducted to assess the rationality of providing and using iron tablets, taking into account variables such as the right patient, right diagnosis, right drug selection, right dose, right method of use, and right interval. The study involved structured interviews with 22 female adolescent respondents and 3 health workers. The data obtained confirmed that iron tablets were provided rationally to female adolescent patients aged 12-18 years, with the right diagnosis and without thalassemia, the right drug selection and dose (ferrous fumarate equivalent to Fe 60 mg, folic acid 0.4 mg), the right method of use, and the right interval of use (once a week). Based on these findings, it was concluded that the Kadatua Timur PKM has provided iron tablets rationally according to existing policies.